2016
DOI: 10.5812/ircmj.30332
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Homocystinuria Misdiagnosed as Moyamoya Disease: A Case Report

Abstract: IntroductionHomocystinuria is a hereditary disease caused by a defect in the enzymes involved in metabolizing methionine. Homocystinuria can influence many systems and may be mistaken for other diseases, including Moyamoya disease. Here, we report the case of a 10-year-old male patient with a diagnosis of Moyamoya disease who had been monitored for that for an extended period. The patient’s diagnosis was changed to homocystinuria as a result of lens subluxation and cataract findings.Case PresentationA 10-year-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In one adolescent girl, who presented with vertical gaze palsy from small thalamic stroke in the distribution of Artery of Percheron, homocysteinemia was the only RF identified. Homocysteinemia has been described as an uncommon RF for stroke in children in general, 3,12,14,33 and in moyamoya disease 34,35 and cervical artery dissection 27,36,37 in particular. Homocysteinemia in these studies resulted from mutations in MFHTR gene.…”
Section: Discussionmentioning
confidence: 99%
“…In one adolescent girl, who presented with vertical gaze palsy from small thalamic stroke in the distribution of Artery of Percheron, homocysteinemia was the only RF identified. Homocysteinemia has been described as an uncommon RF for stroke in children in general, 3,12,14,33 and in moyamoya disease 34,35 and cervical artery dissection 27,36,37 in particular. Homocysteinemia in these studies resulted from mutations in MFHTR gene.…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis is supported by the presence of peripheral atherosclerotic disease, ischaemic heart disease, the relevant risk factors for atherosclerosis and the absence of other predisposing conditions of MMD in the patient samples in our study. On the other hand, one case report of homocystinuria with moyamoya was also described (9), and the possible role of the enzyme activity of methylenetetrahydrofolate reductase (MTFHR), which is associated with hyperhomocysteinemia, in MMD was discussed in the literature (24). A recent study indicated an association between two novel single-nucleotide polymorphisms in the gene regulating homocysteine metabolism (rs9651118 in MTHFR and rs117353193 in TCN2), resulting in increased homocysteine levels in patients with MMD (7,8).…”
Section: █ Discussionmentioning
confidence: 99%
“…There have been reports of moyamoya disease with protein c and protein s deficiency [ 3 , 4 ]. One case report of homocystinuria with moyamoya was also described in the literature [ 5 ]. In our case, there was no clinical feature suggestive of homocystinuria.…”
Section: Discussionmentioning
confidence: 99%